Long-term comparative advantages of the Eurasian Economic Union member states in international trade - Krzysztof Falkowski (International Journal of Management and Economics, 2017)
On 1st January 2015 the Eurasian Economic Union (EAEU) - a new integration block comprising initially Belarus, Kazakhstan, and Russia, and later that year also Armenia and Kyrgyzstan - appeared on the world map. This paper endeavors to identify the EAEU countries' long-term international comparative advantages within four basic groups of goods according to the OECD classification of manufacturing industries based on technology intensity. The analysis, using B. Balassa's RCA methodology and covering the years 2000-2014, indicates that these countries lack competitiveness, with none of them possessing any RCAs in the high-technology category whereas in the medium-hightechnology category - only Belarus. In contrast, all the EAEU countries fared the best in the medium-low-technology category, which is mostly attributable to the resources-based character of their economies. Surprisingly, dramatically low international competitiveness was recorded by Kazakhstan and Russia.
Keywords: F14; O57; P45; 650; international competitiveness; comparative advantages; Eurasian Economic Union